AN INVESTIGATION INTO THE FACTORS INFLUENCING STUDENT DROPOUT RATES IN PAKISTANI UNIVERSITIES - Muhammad Ehtsham; Dr. Nailah Riaz; Dr. Gulnaz Hameed (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the factors that impact student attrition rates in Pakistani universities through the utilization of a mixed-methods methodology. A total of 300 dropout students, 200 current students, 50 teaching members, and 50 administrative personnel were surveyed to collect quantitative data on socio-economic status, academic performance, institutional assistance, and personal obstacles. Furthermore, qualitative observations were gathered from 30 students who dropped out through in-depth interviews and focus group discussions. Each group consisted of 8-10 members. The quantitative data underwent analysis utilizing statistical methodologies, which unveiled noteworthy associations amongst financial matters, familial responsibilities, health concerns, lack of drive, and scholastic achievement. The qualitative data underwent thematic analysis, revealing economic limitations, familial obligations, health concerns, institutional influences, scholastic difficulties, and social context as significant themes. The results emphasize the necessity of implementing focused measures to decrease dropout rates, such as providing more financial assistance, enhancing academic and mental health support, and improving institutional resources and policies.